2007
DOI: 10.1073/pnas.0705673104
|View full text |Cite
|
Sign up to set email alerts
|

Tumor immune escape by the loss of homeostatic chemokine expression

Abstract: The novel keratinocyte-specific chemokine CCL27 plays a critical role in the organization of skin-associated immune responses by regulating T cell homing under homeostatic and inflammatory conditions. Here we demonstrate that human keratinocyte-derived skin tumors may evade T cell-mediated antitumor immune responses by down-regulating the expression of CCL27 through the activation of epidermal growth factor receptor (EGFR)-Ras-MAPKsignaling pathways. Compared with healthy skin, CCL27 mRNA and protein expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
101
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(109 citation statements)
references
References 30 publications
7
101
0
1
Order By: Relevance
“…The expression of chemokine or chemokine receptors may lead to immune tolerance or immune escape, which may, in turn, result in tumor progression. 45,47,48 Our data suggest that decreased interactions between CCR7/CCL21, CCR10/CCL27 and CCL28 may play an important role in CSC-DC vaccinationinduced inhibition of tumor metastasis. We previously reported that blockade of the IL-8 receptor CXCR1 selectively depleted the CSC population.…”
Section: Discussionmentioning
confidence: 92%
“…The expression of chemokine or chemokine receptors may lead to immune tolerance or immune escape, which may, in turn, result in tumor progression. 45,47,48 Our data suggest that decreased interactions between CCR7/CCL21, CCR10/CCL27 and CCL28 may play an important role in CSC-DC vaccinationinduced inhibition of tumor metastasis. We previously reported that blockade of the IL-8 receptor CXCR1 selectively depleted the CSC population.…”
Section: Discussionmentioning
confidence: 92%
“…This is in line with our results showing altered expression of chemokines during the transformation process. Indeed, keratinocytes from human skin tumors exhibited reduced expression of CCL27, a potent attractor of T cells toward the skin (18). Apart from reduced expression during malignant transformation, intratumoral chemokines can also be modified by peroxynitrites, which leads to defective recruitment of T cells to tumor islets (19).…”
Section: Discussionmentioning
confidence: 99%
“…In the tumor cells themselves, antiapoptotic molecules and cytotoxic determinants are upregulated, whereas the Ag-presentation molecule, MHC, is downregulated; moreover, HCC cells secrete various immunosuppressive cytokines, including VEGF, IL-10, and TGF-b (32,33). Among these, IL-10 and TGF-boften produced abundantly in cancer patients-are potent immune suppressors that negatively regulate NK cell function (34,35).…”
Section: Discussionmentioning
confidence: 99%